Environmental quality in underground road tunnel and its relationship with traffic composition - Teo, Jian Yi (2016)
With the rapid development of Singapore’s transport infrastructure, there is an increasing usage of underground spaces for road networks. Hence it is imperative to maintain the sustainable operation of underground networks. Environmental conditions inside the underground road tunnel have a direct impact on motorcyclists, who are directly exposed to pollutants emitted by vehicles. Particulate matters (PMs) suspended in the air could also affect the safety of road users, as PMs reduce visibility levels in the tunnel. Hence, a study carried out on the Kallang-Paya Lebar Expressway (KPE) which runs 12 kilometres (km) long with 9 km of underground tunnels would provide a basis for future studies on underground road networks. A preliminary analysis was carried out to determine environmental conditions in the KPE tunnel, using data provided by the Land Transport Authority (LTA). LTA has installed a Tunnel Management System (TMS) in the tunnel for regular monitoring, which consists of environmental sensors and Closed Circuit Televisions (CCTVs). Environmental parameters being monitored include carbon monoxide (CO) concentration, visibility as well as temperature. CCTV footages were analysed to obtain traffic counts throughout the study period. Relationship between environmental conditions in the tunnel and traffic composition was also derived. To validate the preliminary analysis, a second round of data collection was being conducted by the author, whereby various sets of air sampling instruments were set up in the tunnel for monitoring. Environmental parameters being monitored include CO, carbon dioxide (CO2), nitrogen oxide (NO), particulate matter (PM2.5 and PM10), temperature and relative humidity. Readings collected were analysed, together with traffic data for the corresponding study period provided by the LTA. A set of environmental data for the same period was also obtained from LTA for analysis. From the analysis, it was concluded that CO, CO2 and NO levels correlate with the number of cars. This is due to cars being the majority of the total traffic volume in the tunnel. There was no observable relationship between PM concentration and traffic, as the PM measurements could have been inaccurate due to experimental errors. Temperature and relative humidity were related to the ambient temperature and humidity, rather than to the traffic composition. A wider range of experimental methods could be used for future studies to enhance the accuracy and reliability of the data collected. Regular maintenance of the TMS is also necessary, in order to improve environmental conditions in the tunnel as well as to ensure the safety of motorists. Energy consumption of the TMS could be reduced to ensure sustainability in the tunnel operations.